A cross sectional study to assess nasal carriage of methicillin resistant Staphylococcus aureus in healthcare professionals in a tertiary care hospital - Fibhaa Syed; Nasim Akhtar; Mohammad Ali Arif; Adil Ramzan; Rauf Niazi; Syed ubaid Hasnain; Muhammad Danish Hanif; Sana Asghar; Aamna Naheed (Journal of the Pakistan Medical Association, 2020)
Objective: To determine the nasal carriage of staphylococcus aureus and methicillin-resistant staphylococcus aureus among healthcare workers in a tertiary care setting. Methods: The cross-sectional study was conducted at the Pakistan Institute of Medical Sciences, Islamabad, Pakistan, from April to July 2018, and comprised healthcare workers at the institution. Nasal swabs were collected and cultured on Mannitol salt agar. Mannitol fermenting colonies which were gram-positive cocci, catalase-positive and coagulase-positive were identified as staphylococcus aureus. Antibiotic susceptibility test was performed by modified Kirby-Bauer disc diffusion method. Methicillin resistance was detected using cefoxitin disc diffusion method. Data was analysed using SPSS 23. Results: Of the 210 nasal swabs, 52(24.76%) had a staphylococcus aureus growth, and, of them, 15(7.1%) were methicillin-resistant. No association could be established with either any single category of healthcare worker or an inter-department variation (p>0.05). Likewise, there was no association with age, gender, duration of service, smoking, co-morbidities, use of antibiotics in the preceding six months, treating a patient with methicillin-resistant staphylococcus aureus in the preceding six months and hospitalisation in the preceding year (p>0.05). Conclusion: The frequency of nasal carriage of methicillin resistant staphylococcus aureus amongst healthcare workers was regardless of the nature of their professional engagement. Key Words: Methicillin resistant staphylococcus aureus, Nasal carriage, Continuous...